2000
DOI: 10.1002/(sici)1521-401x(200001)28:1<41::aid-aheh41>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Anion-Exchange Resin Amberlite IRA-93 for the Separation of Arsenite and Arsenate in Aqueous Samples

Abstract: The method described uses the separation of As(III) and As(V) species in aqueous samples by means of the anion‐exchange resin Amberlite IRA‐93. The samples were acidified using acetic acid and passed through a glass column filled with pre‐treated Amberlite IRA‐93 resin. As(III) was poorly adsorbed on the anionic exchanger material, whereas As(V) was retained. The arsenic concentration was measured in the column effluent by graphite furnace AAS (GF‐AAS). The retained As(V) was eluted from the column using 1 M N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Due to these characteristic features sorption technology is the most promising and a fabulous technique for arsenic removal from wastewater [16]. A variety of natural as well as synthetic materials has been tremendously utilized in sorption technology [17][18][19][20]. In this view one of the most magnificent member of macromolecules is "calixarene" has played a pivotal role for decontamination of hazardous materials.…”
Section: Introductionsupporting
confidence: 57%
“…Due to these characteristic features sorption technology is the most promising and a fabulous technique for arsenic removal from wastewater [16]. A variety of natural as well as synthetic materials has been tremendously utilized in sorption technology [17][18][19][20]. In this view one of the most magnificent member of macromolecules is "calixarene" has played a pivotal role for decontamination of hazardous materials.…”
Section: Introductionsupporting
confidence: 57%
“…Arsenate was determined as the difference between total arsenic and arsenite. [23] Calcium was analysed with a flame atomic absorption spectrophotometer (Perkin-Elmer model AAnalyst 200).…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…An applications paper used ion chromatography and then ''offline'' detection with ETAAS. 664 The resin Amberlite IRA-93 was packed into a glass column and then used to separate As III and As V in aqueous samples. It was found that the As III was poorly retained on the column and could be measured directly, but that the As V needed to be eluted with 1 M NaOH.…”
Section: Lc-aasmentioning
confidence: 99%